1988
DOI: 10.1161/01.atv.8.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin stimulates macrophage uptake of low density lipoprotein-heparin-collagen complexes.

Abstract: In this study, we Investigated whether fibronectin will enhance macrophage uptake of participate complexes of low density llpoprotelns (LDL), heparln, and fibrlllar collagen and whether flbronectln's opsonlc effect could be modulated by the heparln component In these model matrices. We Isolated a heparln fraction (Hep Fn ) based on Its affinity to fibronectin. Hep,= n appeared more charged than unfractionated heparln, as evidenced by enhanced electrophoretlc mobility and ability to effect a cathodlc shift in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Aggregates of LDL have also been found to produce foam cells both in vitro and in vivo (5,7). Aggregation can occur via a variety of processes, including oxidation, interaction with phospholipase A 2 and C, sphingomyelinase, glycosylation, interactions with extracellular matrix, and mechanical processes (5,(36)(37)(38)(39)(40)(41)(42)(43)(44). These various aggregation methods all result in different manipulations of the LDL molecule with varying sizes and molecular arrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregates of LDL have also been found to produce foam cells both in vitro and in vivo (5,7). Aggregation can occur via a variety of processes, including oxidation, interaction with phospholipase A 2 and C, sphingomyelinase, glycosylation, interactions with extracellular matrix, and mechanical processes (5,(36)(37)(38)(39)(40)(41)(42)(43)(44). These various aggregation methods all result in different manipulations of the LDL molecule with varying sizes and molecular arrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular fibronectin is important in wound healing and scar formation in the dermis (18) and plays a role in the scarring that characterizes liver cirrhosis (8,9). Plasma fibronectin, which is produced primarily in hepatocytes, plays an important role in clot formation (19), opsonization of bacteria (3), and opsonization of circulating collagenous degradation products (2). The antibody used in this study was raised against a plasma-derived immunogen, but it appears to recognize both cellular and plasma forms of fibronectin based on the staining of nonhepatocyte cell types (endothelial cells, Kupffer cells, macrophages) that are known to produce cellular fibronectin but are not known to produce plasma fibronectin (1,17).…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin is important in a wide variety of fundamental cell processes including cell-to-cell adhesion, cell-to-extracellular matrix adhesion, and cell migration (1). Fibronectin is also found in the plasma, where it is involved in blood clot formation and opsonization (2,3). This functional diversity of the fibronectin gene results from alternative splicing of pre-mRNA, leading to multiple protein isoforms with unique biological properties (4,5).…”
mentioning
confidence: 99%
“…Subsequent in vitro studies showed the affinity of lipoproteins for matrix proteoglycans and collagen fibrils. 11,12 Studies with freeze-etch morphology produced the first clear images of the complex structure of the intima and captured the association of retained lipid with the matrix filaments, including collagen fibrils, first in rabbit models 8 and now in the present study in the apoE-deficient mouse model. Still unclear are the mechanisms by which the matrix filaments and associated collagen fibrils bind lipoproteins or facilitate their transformation and/or oxidation.…”
Section: Discussionmentioning
confidence: 67%